Gas phase proton affinity and basicity of methylated uracil-derivatives - Dávalos-Prado J.Z. (2021)
JRBL acknowledges the support from the Peruvian funding agencies OGI-VRI-UNI ( Oficina de Gestión de Investigación-Vicerrectorado de Investigación U.N.I. ) and CONCYTEC-Master scholarship grant N° 167-2015-FONDECYT-UNI.